Uncoupling Splicing From Transcription Using Antisense Oligonucleotides Reveals a Dual Role for I Exon Donor Splice Sites in Antibody Class Switching - Marchalot, Anne; Ashi, Mohamad Omar; Lambert, Jean-Marie; Carrion, Claire; Lecardeur, Sandrine; Srour, Nivine; Delpy, Laurent; Le Pennec, Soazig (Frontiers in Immunology, 2020)
Class switch recombination (CSR) changes antibody isotype by replacing Cμ constant exons with different constant exons located downstream on the immunoglobulin heavy (IgH) locus. During CSR, transcription through specific switch (S) regions and processing of noncoding germline transcripts (GLTs) are essential for the targeting of Activation-Induced cytidine Deaminase (AID). While CSR to IgG1 is abolished in mice lacking Iγ1 exon donor splice site (dss), many questions remain regarding the importance of I exon dss recognition in CSR. To further clarify the role of I exon dss in CSR, we first evaluated RNA polymerase II (RNA pol II) loading and chromatin accessibility in S regions after activation of mouse B cells lacking Iγ1 dss. We found that deletion of Iγ1 dss markedly reduced RNA pol II pausing and active chromatin marks in the Sγ1 region. We then challenged the post-transcriptional function of I exon dss in CSR by using antisense oligonucleotides (ASO) masking I exon dss on GLTs. Treatment of stimulated B cells with an ASO targeting Iγ1 dss, in the acceptor Sγ1 region, or Iµ dss, in the donor Sµ region, did not decrease germline transcription but strongly inhibited constitutive splicing and CSR to IgG1. Supporting a global effect on CSR, we also observed that the targeting of Iµ dss reduced CSR to IgG3, and to a lesser extent, IgG2b isotypes. Altogether, this study reveals that the recognition of I exon dss first supports RNA pol II pausing and the opening of chromatin in targeted S regions and that GLTs splicing events using constitutive I exon dss appear mandatory for the later steps of CSR, most likely by guiding AID to S regions.